Impaired Nitric Oxide-Mediated Flow-Induced Coronary Dilation in Hyperhomocysteinemia : Morphological and Functional Evidence for Increased Peroxynitrite Formation - Ungvari, Zoltan (American Society for Investigative Pathology, 2002)
Hyperhomocysteinemia (HHcy) is a newly recognized risk factor for myocardial infarction, however, the effect of HHcy on endothelium-dependent flow-induced dilation of coronary arteries is not known. Thus, changes in diameter of small intramural coronary arteries (diameter, ∼145 μm) isolated from control rats and rats with methionine diet-induced HHcy were investigated by videomicroscopy. Increases in intraluminal flow (from 0 to 40 μl/min) elicited dilations of control vessels (maximum, 25 ± 2 μm), responses that were absent in HHcy arteries. The nitric oxide (NO) synthase inhibitor l-NAME inhibited flow-induced dilation of control coronaries, whereas it had no effect on responses of HHcy arteries. Dilations of control and HHcy arteries to the NO donor sodium nitroprusside were not different. Responses to flow in HHcy coronary arteries were unaffected by administration of l-arginine or the prostaglandin H(2)/thromboxane A(2) receptor antagonist SQ 29,548. However, in the presence of superoxide dismutase (plus catalase) or the superoxide scavenger Tiron increases in flow elicited l-NAME-sensitive dilations of HHcy coronaries (maximum, 18 ± 5 μm). Also, superoxide dismutase significantly reduced the enhanced superoxide production of HHcy coronaries (measured by the lucigenin chemiluminescence method). Single vessel Western blotting showed an increased tyrosine nitrosation (a stable biomarker of tissue peroxynitrite formation) in HHcy coronaries. Also, extensive prevalence of 3-nitrotyrosine immunoreactivity was observed in HHcy coronaries that was confined primarily to the subendothelial layers of smooth muscle. We propose that in HHcy an increased level of superoxide scavenges NO forming peroxynitrite, which increases protein nitrosation. The reduced bioavailability of NO impairs flow-induced dilations of coronary arteries, which may contribute to the development of coronary atherosclerosis and ischemic heart disease.